LEXICAL RETRIEVAL PROCESSES AND STRATEGIES IN SECOND LANGUAGE WRITING: A SYNTHESIS OF EMPIRICAL RESEARCH - Manchon, Rosa M.; Murphy, Liz; Roca de Larios, Julio (International Journal of English Studies, 2009)
Lexical access and retrieval are essential processes in fluent and efficient second language (L2) oral and written productive uses of language. In the case of L2 writing, attention to vocabulary is of paramount importance, although the retrieval of relevant lexis while composing in an L2 frequently entails different degrees of problem-solving activity given the lack of (automatic) access to the necessary linguistic resources characteristic of L2 communication. When engaged in this problem-solving behaviour, L2 writers have been reported to deploy a range of L1-based and L2-based lexical retrieval strategies. After situating lexical retrieval processes in cognitive views of written production, the main part of this paper is devoted to a review of the available empirical evidence on lexical retrieval processes and strategies in L2 writing. The paper finishes with some conclusions at the levels of theory and research.